Fiscal Policy Issues in the Aging Societies - Bogetic, Zeljko (2015)
Aging may be one of the most far-reaching processes defining the economic, fiscal, and social changes societies are likely to experience over the next 40 years. The demographic consequences of aging will have a dramatic impact on labor markets, economic growth, social structures--and government budgets. These issues have gained urgency after the second largest global recession in the past 100 years. Based on a broad comparative analysis of countries that include the EU and non-EU European and Central Asian countries, as well as several case studies and model simulations, the paper seeks to provide broad answers--tailored in part to distinct groups of countries according to their aging-fiscal profiles--to major questions facing governments budgets in aging societies: What are the fiscal-aging profiles of Western European, emerging European, and Central Asian countries? In other words, how good or bad is their fiscal situation--"initial conditions"--in view of their emerging aging-related problems? What kind of public spending pressures are likely to emerge in the coming decades, and what will be their relative importance? How do countries compare in terms of the possible impacts of aging on growth and long-term debt sustainability? What can be learned from in-depth and comparative case studies of aging, fiscal sustainability, and fiscal reform? Are there good-practice examples--countries doing things right at the right time--that may offer lessons for the others? And, perhaps most important, given the need for long-term fiscal consolidation for many countries, what kind of revenue and expenditure policy agendas are likely to emerge to mitigate the effects of aging? A key policy conclusion is that countries should aim for early rather than delayed reforms dealing with long-term aging pressures. The urgency is accentuated by the debt situations and/or adverse debt and demographic dynamics in almost all countries but also by the evolving voter preferences. As societies age and voting preferences increasingly reflect the political will of the older population, it will become more difficult to enact the necessary reforms ensuring social and fiscal sustainability.